The use of ICD codes to identify IBD subtypes and phenotypes of the Montreal classification in the Swedish National Patient Register. (2nd April 2020) - Shrestha, Sarita; Olén, Ola; Eriksson, Carl; Everhov, Åsa H.; Myrelid, Pär; Visuri, Isabella; Ludvigsson, Jonas F.; Schoultz, Ida; Montgomery, Scott; Sachs, Michael C.; Halfvarson, Jonas; ,; et al.
Abstract: Introduction: Whether data on International Classification of Diseases (ICD)-codes from the Swedish National Patient Register (NPR) correctly correspond to subtypes of inflammatory bowel disease (IBD) and phenotypes of the Montreal classification scheme among patients with prevalent disease is unknown. Materials and methods: We obtained information on IBD subtypes and phenotypes from the medical records of 1403 patients with known IBD who underwent biological treatment at ten Swedish hospitals and retrieved information on their IBD-associated diagnostic codes from the NPR. We used previously described algorithms to define IBD subtypes and phenotypes. Finally, we compared these register-generated subtypes and phenotypes with the corresponding information from the medical records and calculated positive predictive values (PPV) with 95% confidence intervals. Results: Among patients with clinically confirmed disease and diagnostic listings of IBD in the NPR ( N  = 1401), the PPV was 97 (96–99)% for Crohn's disease, 98 (97–100)% for ulcerative colitis, and 8 (4–11)% for IBD-unclassified. The overall accuracy for age at diagnosis was 95% (when defined as A1, A2, or A3). Examining the validity of codes representing disease phenotype, the PPV was 36 (32–40)% for colonic Crohn's disease (L2), 61 (56–65)% for non-stricturing/non-penetrating Crohn's disease behaviour (B1) and 83 (78–87)% for perianal disease. Correspondingly, the PPV was 80 (71–89)% for proctitis (E1)/left-sided colitis (E2) in ulcerative colitis. Conclusions: Among people with known IBD, the NPR is a reliable source of data to classify most subtypes of prevalent IBD, even though misclassification commonly occurred in Crohn's disease location and behaviour and also among IBD-unclassified patients.